THEORETICAL ASPECTS OF FORMATION OF COMPETITIVE ADVANTAGES OF MANUFACTURING ENTERPRISES IN THE BUILDING INDUSTRY - BENCHUK, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article discusses the theoretical aspects of forming competitive advantages of building industry enterprises in the modern market environment. Growing competition, innovation, digitalization, environmental requirements and economic instability emphasize the need for new approaches to ensuring competitiveness. Various factors of competitive advantage, such as human capital, innovation, social responsibility of business, strategic planning and supply chain management, are analysed. A systematization of factors in four functional blocks is proposed: resources and potential of the enterprise, processes and operational activities, value proposition for the client, market and interaction with clients. The main attention is focused on their impact on product quality, adaptability to environmental changes, and customer satisfaction. It is concluded that competitive advantages are the result of the interaction of numerous factors that need to be integrated into a single strategy to achieve long-term efficiency of enterprises in the construction industry. The article also emphasizes the prospects of studying the impact of technological innovations on the formation of competitive advantages.